Perancangan Gearbox Transmisi untuk Amphibious Articulated All Terrain Vehicle - Firhan Surya Herlambang; Bustami Ibrahim; Wiwik Purwadi; Dadan Heryada Wigenaputra (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2023)
Indonesia is one of the countries with a high level of natural disaster vulnerability, so a good disaster mitigation process is needed. Amphibious Articulated All Terrain Vehicle (AAATV) is designed as one of the solutions to the difficulty of the mitigation process. Amphibious Articulated All Terrain Vehicle is a vehicle with special capabilities that are able to pass through various terrains. Amphibious Articulated All Terrain Vehicle consists of several systems, one of which is the propulsion system. In the Amphibious Articulated All Terrain Vehicle drive system, there is one sub-system, namely the transmission gearbox. This design process uses the VDI 2222 methodology. The design and validation process uses SOLIDWORKS and KISSsoft software. From the design results, it is found that the vehicle will use a Kubota V2203 type diesel engine with a power of 36.4 kW. The desired speed variation is achieved with values of 9.85 km/h, 19.34 km/h, 39.64 km/h, and 10.04 km/h. The design weight is 58.73 kg with dimensions of 346.1 mm x 260 x 347 mm